THE IMPORTANCE OF A PSYCHOLOGICAL-PEDAGOGICAL APPROACH IN DEVELOPING THE SPORTS POTENTIAL OF YOUNG ATHLETES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article scientifically analyzes the importance of a psychological-pedagogical approach in the formation and development of the sports potential of young athletes. The author substantiates how individual psychological characteristics of a person, such as temperament, intellectual ability, interests, and motivation, influence the effectiveness of sports activity. In addition, the content of the concepts of ability and talent, their general and specific types, and the factors of their formation are described. The article also analyzes the importance of psychological diagnostics in the field of sports, as well as the role of pedagogical activity in identifying and developing sports abilities among youth. The research results show that the interrelation of an individual approach, social environment, and psychological support in sports activities is an important factor in enhancing the sports potential of young people.